The Role of Information Science in the Development of Science and Technology - Nazwan Lidjali; Deitje. S. Pongoh; Aldrin Tongkotou; Nadine Sondak; Sebastian Mewaikere; Prisilia Baduang (Jurnal Syntax Admiration, 2024)
Information Science has become a pivotal force driving progress in science and technology. In today's era, Information and Communication Technology (ICT) plays a significant role in enhancing organizational efficiency and enabling individual growth. By facilitating seamless communication and data management, ICT allows businesses to optimize their relationships with clients, suppliers, and distributors. Moreover, ICT has transformed education, empowering learners to access resources globally and enabling personalized learning experiences. Informatics, as an interdisciplinary field, encompasses computer science, information systems, and data analytics, all of which contribute to solving complex challenges. This paper explores the diverse applications of Informatics and its role in shaping a technologically advanced society. Through its integration across various sectors, Informatics not only drives innovation but also bridges the gap between technological potential and practical implementation